A framework of artificial intelligent for investment assessment in coastal and small island area, relate to disaster risk. Issue 1 (April 2021) - Yonvitner; Agus, S B; Perdinan; Ramadhani, R A; Wicaksana, B A
Abstract: Coastal areas and small islands in Indonesia have reliable investment feasibility potential. The location of small islands that must be developed must assess the ecosystem's carrying capacity and the environment, including disaster risk. Research on investment feasibility based on disaster risk is necessary to support small islands' investment plans and development. This area is known as a vulnerable and potentially high risk from natural or human-made disasters. The research conducted in the Kepulauan Seribu will adopt digital technology to assess the eligibility criteria as the start of an investment step. The intervention of digital technology on investment feasibility assessment in line with the digital era in the Industrial Revolution 4.0. The outputs of the research are (1) investment feasibility indicators in coastal areas and small islands based on disaster risk; (2) strengthening systems and institutions related to investment feasibility assessment in coastal areas and small islands; (3) the prototype of smart system technology for assessing investment feasibility in coastal areas and small islands based on disaster risk as part of the adaptation of revolution 4.0 to support the policy of integrated electronic business licensing services.